Fatores socioeconômicos e percepção de risco de produtores de gado de corte no uso de produtos veterinários - Alves, Joice de Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The sanitary practices of beef cattle farmers have immediate reflections on animal health and bring potential risks to public health and the environment. Therefore, the aim of this study was to verify the risk perception in 90 farmers from 66 towns in the State of São Paulo, in matters related to the purchase and management of veterinary products. Through qualitative approach, personal interview ─ using open and closed questions, and multiple correspondence analysis, it was verified tendencies of associations between socioeconomic factors and the perception of the farmers. The addressed issues were about the observation of the grace period of veterinary products, the mention of the grace period of two veterinary products in use in the property, which criterion is used to decide on the purchase of veterinary products, the estimating of body weight or actual weighing of animals upon deworming and whether the person who administer the veterinary products has received any kind of training or not. Farmers with complete or incomplete elementary education tend to adopt practices judged as improper or unsuitable; they do not estimate body weight or conduct the actual weighing of animals upon deworming and do not take part in training activities for the administration of products. Farmers with secondary education tend not to observe the grace period of products and spontaneously name price or quality as criterion to decide on the purchase of products. On the other hand, farmers with higher education correctly answered the grace period of two veterinary products, tend to estimate or weight the animals upon administration of products and participate or develop training activities. When the farmers were grouped according to the total number of their herd, the tendencies revealed that professional advice is the criterion employed by farmers with herds of up to 100 animals; however, they do not estimate body weigh...
Keywords: Bovino - Criação; Drogas - Efeitos colaterais; Drogas veterinarias; Vigilância sanitária; Saneamento rural; Segurança alimentar; Drug residues